Inscription funéraire trouvée à Gondreville (Loiret, cité des Sénons) - Monique Dondin‑Payre; Camille Scaon (Revue Archéologique du Centre de la France)
During the rescue archaeology operations on the A19 motorway, a little funerary building was found near a Roman road, in the commune of Gondreville (Loiret). Next to it, probably in the destruction layer, was discovered a funeral inscription, which was undoubtedly associated with it.